2013
DOI: 10.1177/0885328213508165
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive bredigite coating with improved bonding strength, rapid apatite mineralization and excellent cytocompatibility

Abstract: Previous studies have shown that bredigite (Ca7MgSi4O16) bioceramics possessed excellent biocompatibility, apatite-mineralization ability and mechanical properties. In this paper, the bredigite coating on Ti-6Al-4 V substrate was prepared by plasma spraying technique. The main compositions of the coating were bredigite crystal phase with small parts of amorphous phases. The bonding strength of the coating to Ti-6Al-4 V substrate reached 49.8 MPa, which was significantly higher than that of hydroxyapatite coati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…It was found that the apatite peaks (at approx. 2u ¼ 25.58, 32.18, 42.48 and 49.48) appeared on all the samples [5], and other peaks appeared at approximately 2u ¼ 20.88, 23.58, 29.28 and 47.98, which belong to the cements. Clearly, the intensity of the peaks for 40 m-CSBC (figure 6a) and 20 m-CSBC (figure 6b) were significantly higher than CSBC (figure 6c), which was in accord with the SEM images.…”
Section: Degradability Of Cementsmentioning
confidence: 90%
See 1 more Smart Citation
“…It was found that the apatite peaks (at approx. 2u ¼ 25.58, 32.18, 42.48 and 49.48) appeared on all the samples [5], and other peaks appeared at approximately 2u ¼ 20.88, 23.58, 29.28 and 47.98, which belong to the cements. Clearly, the intensity of the peaks for 40 m-CSBC (figure 6a) and 20 m-CSBC (figure 6b) were significantly higher than CSBC (figure 6c), which was in accord with the SEM images.…”
Section: Degradability Of Cementsmentioning
confidence: 90%
“…These characteristics made them one of the most intriguing materials in the biomedical field. The bredigite (Ca 7 MgSi 4 O 16 ) with apatite layer induced in simulated body fluid (SBF) could support cell attachment and stimulate cell proliferation and differentiation [5]. It was reported that some ions (such as calcium, magnesium and silicon) released from these bioceramics could change the biological environment in vivo and promote bone reconstruction [6].…”
Section: Introductionmentioning
confidence: 99%
“…Bredigite, a silicate‐based bioceramic, has received significant attention because it can release bioactive ions and trigger specific cellular responses during tissue engineering . Bredigite possesses an advantage due to its relatively stable chemical and physical properties and controllable ion release compared with growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…34 Bredigite, a silicate-based bioceramic, has received significant attention because it can release bioactive ions and trigger specific cellular responses during tissue engineering. 35 Bredigite possesses an advantage due to its relatively stable chemical and physical properties and controllable ion release 13 compared with growth factors. The release of bredigite ions after exposure to a physiological environment is well-defined and easy to control at the molecular level, 36 contributing to the validity of our results.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In addition, bredigite and its coating could promote the formation of bone-like apatite on material surface after soaking into stimulated body fluid. 8 Moreover, the osteoblasts could adhere and spread well on the surfaces of bredigite bioceramics, and the ionic product dissolution from bredigite obviously stimulated cell proliferation. 9,10 Therefore, bredigite-based biomaterials might open new possibilities for bone repair.…”
Section: Introductionmentioning
confidence: 99%